Reactive Distillation Simulation For Production Of Methyl Acetate Kinetic Model Parameter Optimization - Rohaimi, Ahmad Firdaus Mohamad (Universiti Sains Malaysia, 2022)
Due to the numerous benefits of the reactive distillation column (RD) in chemical synthesis over standard method (reactors followed by distillation columns), RD has drawn the attention of researchers all over the world to explore its potential in the chemical industries. Implementing RD as process intensification (PI) technology can overcome the disadvantages of the conventional distillation column. The modeling, simulation, and optimization of the RD on the esterification process of acetic acid and methanol are used for producing methyl acetate have been carried out by using Aspen Plus V10. RadFrac packed column was developed and simulated which had the reaction and separation in one column with 23 stages included reboiler and condenser. Moreover, the Non-Random Two Liquid (NRTL) property method, feed flowrate of acetic acid and methanol of 0.03L/min, feed temperature of 25°C, and pressure of 1 atm respectively was used. Sensitivity and optimization tools in Model Analysis Tools were used simultaneously in the optimization of kinetic parameters and operating parameters respectively. Optimization of kinetic parameters such as K-stoichiometry A and K-stoichiometry B were studied to get good convergence with the data of Giwa (2013). To maximize the purity of methyl acetate, operating parameters such as feed flowrate, reflux ratio, and reboiler heat duty are studied and optimized. Optimized results showed the optimum condition to maximize the purity of methyl acetate is at methanol flowrate of 0.0472266kmol/hr, reflux ratio of 9, and reboiler heat duty of 528.5Watt. A comparison between Giwa (2013) and the present study on RD column was carried out by comparing conversion, purity, and reboiler heat duty. The purity of methyl acetate increased by 50.7% from 0.653108 to 0.984221 as well as the reboiler heat duty is minimized by about 57.14% from 700Watt to 528.5Watt but the conversion is reduced by 30% from 96.48% to 66.28%. In above mentioned operating variables, the feed flowrate, the reflux ratio, and reboiler heat duty have the most significant effect on the purity of methyl acetate in the distillate and the acetic acid conversion. Moreover, the objective function of this optimization was achieved as the estimated optimum value of feed flowrate, reflux ratio, and reboiler heat duty were used to rum the developed model. Thus, this objective proved that the Aspen Plus optimum values were validated.